TV, computer, tablet and smartphone use and autism spectrum disorder risk in early childhood: a nationally-representative study - Maria Melchior; Katharine Barry; David Cohen; Sabine Plancoulaine; Jonathan Y. Bernard; Karen Milcent; Malamine Gassama; Ramchandar Gomajee; Marie-Aline Charles (BMC, 2022)
Abstract Background Screen media use in early childhood has largely increased in recent years, even more so during the COVID-19 epidemic, and there is much discussion regarding its influence on neurodevelopment, including Autism Spectrum Disorder (ASD). Methods We examined the relationship between use of TV, computer, tablet and smartphone at age 2 years and risk of ASD assessed in telephone-based questionnaires among 12,950 children participating in the nationally representative ELFE ('Etude Longitudinale Française sur les Enfants') birth cohort study in France. Results In inverse-probability weighted (IPW) multinomial regression analyses, children's weekly or daily screen media use was associated with an increased likelihood of an intermediate risk of ASD (IPW-controlled OR for weekly use:1.07, 95% CI 1.02-1.12; IPW-controlled OR for daily use:1.05, 95% CI 1.02-1.08) but inversely associated with a high risk (IPW-controlled OR for weekly use: 0.60, 95% CI 0.50-0.73; IPW-controlled OR for daily use: 0.75, 95% CI 0.62-0.91), as ascertained by the M-CHAT. This was confirmed when studying TV as well as computer/tablet exposure separately. Conclusions Overall, our nationally-representative study conducted among a large sample of 2-year-old children, indicates a complex relationship between screen exposure and ASD risk.